Risk factors for drug-drug interactions in patients with psychiatric disorders - Ranković, Anica; Milentijević, Iva; Janković, Slobodan (Archives of Pharmacy, 2022)
Other chronic diseases are often present in patients with mental illness. For this reason, many patients with psychiatric disorders use multiple medications. As the number of patients' medications increases, so does the possibility of adverse drug reactions, especially those caused by drug interactions. The aim of this study was to investigate the prevalence of potential drug-drug interactions (pDDIs) in hospitalized patients with psychiatric disorders and to identify factors associated with their occurrence. The research was designed as an observational, retrospective, cohort study conducted at the Clinic for Mental Disorders "Dr Laza Lazarevic", Belgrade. Medscape®, Epocrates® and Lexicomp® bases were used to detect potential drug interactions among inpatients. The study included 511 patients, 44.63 ± 11.81 years old. The average number of pDDIs per patient ranged from 5.9 ± 4.7 (Medscape), and 8.2 ± 5.4 (Epocrates) to 8.5 ± 5.1 (Lexicomp). The following risk factors were identified by all three interaction checkers used: CRP, number of pharmacological subgroups, number of prescribed drugs, the total number of diagnoses recorded during the hospitalization, antiepileptics, antibiotics, antacids, vitamins, number of comorbidities, route, form and dose of the drug. Numerous other studies have demonstrated a positive correlation between pDDIs and an increased number of drugs, length of hospitalization and more comorbidities in patients (1,2). The identified risk factors will serve to define the subpopulation of patients at high risk for interactions, as well as to plan the introduction of monitoring for early detection of interactions.